Design and Implementation of Energy Internet Big Data System Based on Blockchain. Issue 3 (March 2021) - Yang, Dongwei; Fu, Yuchen; Zheng, Kaifa; Zheng, Shangzhuo; Liu, Zexin
Abstract: Blockchain is a new application model that integrates distributed data storage, point-to-point transmission, consensus mechanism, encryption algorithm, and other computer technologies. These technologies make blockchain traceable, reliable, and resistant to modification, characteristics that suit the need for data storage and exchange. As a result, in this paper, we design an energy internet big data system based on energy and blockchain technology systematically. Firstly, we discuss the basics that support for energy scheduling and policymaking of the management department, including energy data coordination, enterprise monitoring, and consumption monitoring, and trading services. Secondly, we develop the Unified Energy Reporting Service. It can generate the energy demand and supply table, production and sales table, demand forecast table, energy consumption monitoring table, environmental protection monitoring data, and energy data of critical customers. Finally, we ensure the storage and collection of evidence in our system, which would guarantee the electric security of the Winter Olympic Games.